Highly selective fluorescence imaging of zinc distribution in HeLa cells and Arabidopsis using a naphthalene-based fluorescent probe. Issue 35 (1st April 2015) - Lee, Ji Ha; Lee, Jin Hyeok; Jung, Sung Ho; Hyun, Tae Kyung; Feng, Mingxiao; Kim, Jae-Yean; Lee, Jae-Hong; Lee, Hoyeon; Kim, Jong Seung; Kang, Chulhun; Kwon, Ki-Young; Jung, Jong Hwa
Abstract : 2-( N, N -Dimethylamino)naphthalene-based probe1 was found to exhibit a dramatic enhancement in fluorescence upon addition of Zn 2+, but not with any other metal ions. Abstract : 2-( N, N -Dimethylamino)naphthalene-based probe1 was found to exhibit a dramatic enhancement in fluorescence upon addition of Zn 2+, but not with any other metal ions. Probe1 as a chemoprobe enabled high-resolution fluorescence imaging of zinc ions in HeLa cells and Arabidopsis .